2018
DOI: 10.1016/j.redox.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of short chain fatty acids on endothelial Nlrp3 inflammasome activation and neointima formation: Antioxidant action of butyrate

Abstract: Short chain fatty acids (SCFAs), a family of gut microbial metabolites, have been reported to promote preservation of endothelial function and thereby exert anti-atherosclerotic action. However, the precise mechanism mediating this protective action of SCFAs remains unknown. The present study investigated the effects of SCFAs (acetate, propionate and butyrate) on the activation of Nod-like receptor pyrin domain 3 (Nlrp3) inflammasome in endothelial cells (ECs) and associated carotid neointima formation. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 85 publications
1
66
0
4
Order By: Relevance
“…Generally speaking, the activation of the NLRP3 inflammasome involves two steps ( Sutterwala et al, 2014 ; Shao et al, 2015 ; Wu et al, 2018a ; Yuan et al, 2018 ; Figure 1 ). In the first step, a priming signaling is triggered by certain PAMPs or DAMPs on Toll-like receptor 4 (TLR4), which leads to the activation of the NF-κB-mediated pathway.…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
“…Generally speaking, the activation of the NLRP3 inflammasome involves two steps ( Sutterwala et al, 2014 ; Shao et al, 2015 ; Wu et al, 2018a ; Yuan et al, 2018 ; Figure 1 ). In the first step, a priming signaling is triggered by certain PAMPs or DAMPs on Toll-like receptor 4 (TLR4), which leads to the activation of the NF-κB-mediated pathway.…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
“…The anti-inflammatory activity of SCFAs has been also evaluated in vivo: in a partially ligated carotid artery (PLCA) mouse model of atherosclerosis, it has been found that butyrate repressed endothelial Nlrp3 (Nlr family pyrin domaincontaining 3) inflammasome activation in ECs, via redox signaling pathways, and prevented arterial neointima formation. On the contrary, acetate and propionate exerted minimal inhibitory effects on inflammasome activation and even seem to augment the arterial neointima formation in the PLCA model [117]. The antiatherosclerotic activity of SCFAs was also confirmed by a recent study by Chen and collaborators showing that SCFAs from pectin fermentation are able to inhibit intestinal cholesterol absorption, to decrease serum total and low-density lipoprotein cholesterol and to protect ApoE -/against diet-induced atherosclerosis [118].…”
Section: Flavonoidsmentioning
confidence: 84%
“…SCFAs inhibit the production of proinflammatory cytokines and the recruitment of immune cells to ECs, mechanisms mediated by binding to the free fatty acid (FFA) receptor types 2 and 3 and G-protein-coupled receptor 109A (GPR109A) and by inhibiting intracellular activity of histone deacetylases (HDACs), enzymes which can regulate multiple molecular processes involved in atherogenesis [97,[113][114][115]. Recently, it has emerged that SCFAs inhibit LPS-and TNFα-induced endothelial expression of VCAM-1, through activation of GPR41/43, which are SCFA receptors expressed in ECs, and inhibition of HDAC activity [116,117]. The anti-inflammatory activity of SCFAs has been also evaluated in vivo: in a partially ligated carotid artery (PLCA) mouse model of atherosclerosis, it has been found that butyrate repressed endothelial Nlrp3 (Nlr family pyrin domaincontaining 3) inflammasome activation in ECs, via redox signaling pathways, and prevented arterial neointima formation.…”
Section: Flavonoidsmentioning
confidence: 99%
“…However, oral supplementation of butyrate can reverse these changes and inhibit VSMC proliferation, migration, and cell cycle progression in a dose-dependent manner in vitro. Butyrate also inhibits superoxide production and consequent Nod-like receptor pyrin domain 3 (Nlrp3) inflammasome formation and activation, which is beneficial against vascular inflammation or intimal hyperplasia [126]. These studies suggest that the association of gut microbial composition with arterial remodelling could potentially occur through an inhibitory effect of butyrate on VSMCs [125].…”
Section: Gut Microbiota Derived Metabolites and Arterial Remodellingmentioning
confidence: 95%